Characteristics of High-Risk Behaviours Related to Alcohol and Illicit Drug Use and their Associated Factors among Adolescents in Middle and High School - Widjaja, Melanie; Latief, Abdul; Sekartini, Rini (Medicinus, 2024)
Background: Use of narcotics, psychotropic and addictive substances (NPA) in adolescents has become one of the major social problems we are facing in society and it gives a negative impact. This study was done to determine the characteristics and factors that influence high-risk behaviour of NPA use in adolescents in middle and high school, also introducing CRAFFT questionnaire as an early screening tool for alcohol an illicit drugs use.Methods: Quantitative study (validated questionnaire) was conducted among 514 subjects aged 12-18 years old. CRAFFT questionnaire was used to detect a high-risk behavior of alcohol and illicit drugs use and self-reported questionnaire used to determine the risk factors of NPA.Result: Most participants (19,6%) were involved in high-risk behaviour of alcohol and illicit drugs, with the majority was males (12,4%). This study showed smoking behaviour (23,8%), drinking alcohol (15,8%) and illicit drugs use (13,6%). The type of drugs being used were cannabis (52,7%), tramadol (15,2%), dextromethorphan (10,7%) and methamphetamine (6,3%). CRAFFT questionnaire has a good internal consistency with Cronbach’s α 0,73. Education level, authoritarian parenting style, unharmonious parents, peer pressure or threat, and extracurricular activities were factors that influenced high-risk behavior of alcohol and illicit drug useConclusions: Early detection, comprehensive treatment, and intervention of risk factors of NPA use are needed. CRAFFT can be use as one of the screening tools for detection of alcohol and illicit drugs use in adolescents.